Effects of PTH on osteoblast bioenergetics in response to glucose - Victoria E. DeMambro; Li Tian; Vivin Karthik; Clifford J. Rosen; Anyonya R. Guntur (Bone Reports, 2023)
Parathyroid hormone acts through its receptor, PTHR1, expressed on osteoblasts, to control bone remodeling. Metabolic flexibility for energy generation has been demonstrated in several cell types dependent on substrate availability. Recent studies have identified a critical role for PTH in regulating glucose, fatty acid and amino acid metabolism thus stimulating both glycolysis and oxidative phosphorylation. Therefore, we postulated that PTH stimulates increased energetic output by osteoblasts either by increasing glycolysis or oxidative phosphorylation depending on substrate availability. To test this hypothesis, undifferentiated and differentiated MC3T3E1C4 calvarial pre-osteoblasts were treated with PTH to study osteoblast bioenergetics in the presence of exogenous glucose. Significant increases in glycolysis with acute ∼1 h PTH treatment with minimal effects on oxidative phosphorylation in undifferentiated MC3T3E1C4 in the presence of exogenous glucose were observed. In differentiated cells, the increased glycolysis observed with acute PTH was completely blocked by pretreatment with a Glut1 inhibitor (BAY-876) resulting in a compensatory increase in oxidative phosphorylation. We then tested the effect of PTH on the function of complexes I and II of the mitochondrial electron transport chain in the absence of glycolysis. Utilizing a novel cell plasma membrane permeability mitochondrial (PMP) assay, in combination with complex I and II specific substrates, slight but significant increases in basal and maximal oxygen consumption rates with 24 h PTH treatment in undifferentiated MC3T3E1C4 cells were noted. Taken together, our data demonstrate for the first time that PTH stimulates both increases in glycolysis and the function of the electron transport chain, particularly complexes I and II, during high energy demands in osteoblasts.